Free Vibration of Annular Plates Constrained by Translational and/or Rotational Springs on Outer and Inner Edges - Narita, Yoshihiro (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2023)
This paper presents comprehensive lists of natural frequencies for vibration of thin isotropic annular plates with outer and inner edges elastically constrained by translational and rotational springs. A method is extended from a previously presented Ritz approach to include effects of the springs. In numerical examples, sixteen models are considered to cover all general cases of locating translational and/or rotational springs on outer and/or inner edges in addition to classical boundary conditions of free and simple supported edges. After convergence study and comparison test in specific cases are made to validate solution accuracy, frequency parameters of the sixteen models are summarized and frequency variations with increasing spring stiffness are illustrated.